Constructing a pesantren halal hub model based on the penta helix framework for developing the halal economy in Indonesia - Abdul Rachman; Mariya Ulpah; Bilaly Sangare (Indonesian Journal of Islamic Economics Research, 2026)
This study examines the construction of a Pesantren Halal Hub model based on the Penta Helix framework as an innovation for developing the halal economy in Indonesia, considering the substantial number of pesantren, namely 42,433 Islamic boarding schools in the 2024/2025 academic year, and the significant growth of the global halal economy, which is projected to reach USD 3.36 trillion by 2028 (SGIE 2024/2025). This number represents a considerable potential for building a pesantren-based halal industry ecosystem. However, the involvement of pesantren in the halal industry ecosystem remains limited due to constraints such as limited access to capital, inadequate managerial skills, challenges in obtaining halal certification, and weak connectivity to global markets. This research employs a descriptive qualitative method with a Penta Helix approach. The findings reveal that the Pesantren Halal Hub model constitutes an innovative strategy for developing Indonesia’s halal economy, as it enhances the number of halal-certified pesantren products, expands market access through halal hubs and halal e-commerce, strengthens cross-sectoral collaboration networks, and supports financing mechanisms based on productive waqf and Islamic social finance (ZISWAF). Accordingly, collaboration among pesantren, government, industry, universities, communities, and Islamic social finance institutions (ZISWAF) is crucial in constructing the Pesantren Halal Hub model. Theoretically, this research enriches the literature on the integration of Islamic educational institutions into the Penta Helix innovation model, while practically, it provides policy recommendations and an implementable model that can be replicated by government, industry, and pesantren across various regions